Recyclable Periodic Nanostructure Formed by Sublimable Liquid Crystals for Robust Cell Alignment - Shin, Min Jeong (Langmuir : the ACS journal of surfaces and colloids, 2022)
We demonstrate a facile method to fabricate a recyclable cell-alignment scaffold using nanogrooves based on sublimable liquid crystal (LC) material. Randomly and uniaxially arranged smectic LC structures are obtained, followed by sublimation and recondensation processes, which directly produce periodic nanogrooves with dimensions of a couple of hundreds of nanometers. After treatment with osmium tetroxide (OsO4), the nanogroove can serve as a scaffold to efficiently induce directed cell growth without causing cytotoxicity, and it can be used repeatedly. Together, various cell types are applied to the nanogroove, proving the scaffold's broad applicability. Depending on the nanotopography of the LC structures, cells exhibit different morphologies and gene expression patterns, compared to cells on standard glass substrates, according to microscopic observation and qPCR. Furthermore, cell sheets can be formed, which consist of oriented cells that can be repeatedly formed and transferred to other substrates, while maintaining its organization. We believe that our cell-aligning scaffold may pave the way for the soft material field to bioengineering, which can involve fundamentals in cell behavior and function, as well as applications for regenerative medicine